2006
DOI: 10.1017/s0012162206001745
|View full text |Cite
|
Sign up to set email alerts
|

Initial development and validation of the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD)

Abstract: This paper reports the development and validation of a disease-specific measure of health status and well-being of children with severe cerebral palsy (CP). The Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) was constructed from recommendations from caregivers, healthcare providers, and review of other measures. Items spanning six domains are rated on an ordinal scale. Standardized scores (0-100) are reported for each domain and in total. Primary caregivers (n = 77) of 45 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
188
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 22 publications
2
188
1
4
Order By: Relevance
“…7,8,10,22 This study has shown that nonoperative treatment for children with GMFCS level IV/V CP and a significant scoliosis was associated with a small decrease in carer-assessed QoL during childhood. Spinal fusion was associated with an increase in QoL.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…7,8,10,22 This study has shown that nonoperative treatment for children with GMFCS level IV/V CP and a significant scoliosis was associated with a small decrease in carer-assessed QoL during childhood. Spinal fusion was associated with an increase in QoL.…”
Section: Discussionmentioning
confidence: 77%
“…23 Children in our study had low baseline CPCHILD scores; worse than would be present in a representative population of children with GMFCS level IV or V CP without scoliosis. 10 Thus when compared with historical controls, 10,24 this study would suggest carer-assessed QoL for children with GMFCS level IV/V CP and scoliosis is less than for those with GMFCS level IV/V CP and no scoliosis.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In Ergänzung zu den positiven Erfahrungen in der Literatur konnte mit den hier vorgestellten Ergebnissen die Wirksamkeit dieser Therapieoption auch bei Patienten mit progredienten neurodege- [4], Care and Comfort Hypertonicity Questionnaire (CCHQ) [25], Caregivers Priorities and Child Health Index of Life with Disabilities (CPCHILD) [24]). Für die vorliegende Anwendungsbeobachtung ist kritisch anzumerken, dass derartige Messinstrumente zur standardisierten Erfassung des Therapieeffektes erst im Verlauf Anwendung fanden und deshalb hier noch nicht in die Auswertung einbezogen werden konnten.…”
Section: Diskussionunclassified